293 Impact of metabolic syndrome on coronary microvascular dysfunction: a single-centre experience. (8th December 2021) - Martello, Marco; Testa, Gabriella; Novo, Salvatore; Novo, Giuseppina; Galassi, Alfredo R; Sucato, Vincenzo
Abstract: Aims: The purpose of this study was to evaluate whether microvascular dysfunction is more present in patients with metabolic syndrome (MetS) compared to diabetics and hypertensive patients with two angiographic imaging methods, to evaluate the degree of microcirculation dysfunction, the TIMI frame count and Myocardial Blush grade. Both techniques of rapid use and relatively cheap, and allow us to have a good degree of evaluation referred to the function of the coronary microcirculation. Methods and results: The study included 445 patients allocated into three groups, 157 in the MetS group, 128 in the diabetics group, and 160 patients in the hypertensive group. All patients accessed to the emergency room for anginal chest pain, all were hospitalized in the cardiac intensive care unit from 2015 to 2020. Inclusion criteria were the presences of chest pain and/or their positive stress test, and epicardial coronary arteries free from stenosis at coronary angiography. We compared the results obtained from the angiographic techniques (TIMI Frame Count and Myocardial Blush Grade) in the two subgroups: MetS vs. hypertensive, and MetS vs. diabetics. In the first subgroup, we analyzed the TFCs of the three vessels in patients with hypertension and comparing them with patients with MetS, we observed that the latter have a worse perfusion condition: the three epicardial coronary vessels have a higher TFC than the hypertensive population (TFC LAD 33.1 ± 5.6 vs. 28.4 ± 5.6, P  = 0.018), (TFC RCA 27.2 ± 5.2 vs. 23.1 ± 5.2, P  = 0.014) (TFC CX 27.9 ± 5.4 vs. 26.9 ± 5.4, P  = 0.03). That indicates slow flow in patients with MetS coronary microcirculation. Analyzing the MBG, however, in the three coronary vessels of patients with hypertension compared to patients with metabolic syndrome, no difference was found in terms of worsening of the coronary microcirculation. Finally comparing the indices that summarize the values of the individual arteries both for the TFC and MBG, was seen as the TMBS is reduced in both groups (7.1 ± 0.49 vs. 7.1 ± 0.6, P -value = 0.04). The TTFC is instead higher in patients with MetS (83.9 ± 5.8 vs. 77.8 ± 6.7, P -value =0.024). Then we performed the same type of comparison between MetS and type 2 diabetic subgroup, in this comparison we observed how by analyzing the TFCs of the three coronary vessels, MetS patients have a slower coronary flow than patients with type 2 diabetes mellitus (TFC LAD 33.1 ± 5.6 vs. 30.6 ± 6.2, P  = 0.04), (TFC RCA 27.2 ± 5.2 vs. 25 ± 5.3, P  = 0.02), (TFC CX 27.9 ± 5.4 vs. 27.2 ± 5.6, P  = 0.05). Comparing MBG of the three coronary vessels instead, the flow is lower in diabetic patients TTFC was higher in patients with metabolic syndrome (83.9 ± 5.8 vs. 82.7 ± 8.6, P -value = 0.02). While TMBS was lower in diabetic patients than in patients with metabolic syndrome (7.1 ± 0.49 vs. 6.7 ± 0.74, P -value = 0.01). Conclusions: This study shows that patients with MetS had a major coronary microvascular dysfunction using TFC imaging technique, analysis compared to diabetics or hypertensive patients, these differences resulted to be statistically significant. A clinical evaluation of this parameters using TFC such in this study, might give further information about (CMD) in this patients in order to act to develop the best treatment to this patients and to improve their clinical condition.